2015
DOI: 10.1038/nature14472
|View full text |Cite
|
Sign up to set email alerts
|

A Middle Triassic stem-turtle and the evolution of the turtle body plan

Abstract: The origin and early evolution of turtles have long been major contentious issues in vertebrate zoology. This is due to conflicting character evidence from molecules and morphology and a lack of transitional fossils from the critical time interval. The ∼220-million-year-old stem-turtle Odontochelys from China has a partly formed shell and many turtle-like features in its postcranial skeleton. Unlike the 214-million-year-old Proganochelys from Germany and Thailand, it retains marginal teeth and lacks a carapace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
127
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 20 publications
4
127
0
3
Order By: Relevance
“…The scant fossil record of stem-turtles (i.e., non-Testudines Testudinata) has further obscured the evolutionary origin of this group. Recent discoveries of new species and reanalysis of existing specimens with novel methodological approaches (e.g., computed tomography and digital visualization) have provided new data to the debate of turtle ancestry (Li et al, 2008;Bever et al, 2015;Schoch and Sues, 2015). These studies found support for the diapsid origin of turtles and produced potential evidence for closure of the temporal fenestrae early in their evolutionary history (Schoch and Sues, 2015;Werneburg, 2015;Lyson et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The scant fossil record of stem-turtles (i.e., non-Testudines Testudinata) has further obscured the evolutionary origin of this group. Recent discoveries of new species and reanalysis of existing specimens with novel methodological approaches (e.g., computed tomography and digital visualization) have provided new data to the debate of turtle ancestry (Li et al, 2008;Bever et al, 2015;Schoch and Sues, 2015). These studies found support for the diapsid origin of turtles and produced potential evidence for closure of the temporal fenestrae early in their evolutionary history (Schoch and Sues, 2015;Werneburg, 2015;Lyson et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, the morphology of the ribs, as well as the more rigid body wall, powerful forelimbs and triangular skull, have been considered to represent adaptations to fossoriality in E. africanus (Lyson et al, 2016). On the other hand, the type localities of both P. rosinae and O. semitestacea have also yielded terrestrial taxa (Joyce, 2015;Schoch and Sues, 2017) and, in fact, terrestrial diapsid remains are dominant at the type locality of the former (Schoch and Sues, 2015). Additionally, Joyce (2015) argued in favor of Odontochelys semitestacea as a terrestrial proto-turtle, based on its phalangeal formula.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oldest, fully-shelled turtles were likely terrestrial (Joyce and Gauthier 2004;Scheyer and Sander 2007;Schoch and Sues 2015). However, extensive use of aquatic habitats became pervasive soon thereafter, to the extent that, among living turtles, all terrestrial lineages are nested within primarily aquatic clades (Gosnell et al 2009).…”
Section: Introductionmentioning
confidence: 99%